Characters in Traditional Games; Analysis of Literature Related to Character Values Developed in Children Through Traditional Games - Nurhidayah, Nurhidayah; Lumbantobing, Panni Ance; Roziah, Roziah; Santi, Yulia; Ahmadi, Dedi (Widyagogik, 2024)
Traditional games are folk games that are inherited or developed from generation to generation in a particular area or culture. Traditional games are usually played in groups indoors or outdoors using simple equipment available in the surrounding environment with a fun nature. This study aims to identify and analyze children's characters developed through the application of traditional games. The type of qualitative research with descriptive analysis methods. Literature review of relevant journal articles from Google Scholar , articles are limited to publications in 2024 with the search keywords "character education, character, traditional games and children" is a data collection technique in this study. The focus of the study is a literature review of various types of traditional games and the character values of children developed through these games. Traditional games are not only a means of entertainment, but also contain character values that are important for the formation of good personality and social interaction in children. Based on the Analysis of Character Values in the journal on the formation of children's character through traditional games in 2024, eleven character values were obtained, including the characters of honesty, sportsmanship, justice, responsibility, cooperation, discipline, creativity, hard work, independence, control or self-control and tolerance.